2023
DOI: 10.1177/10711007231156424
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Curve for Patients With Pilon Fractures Using Patient-Reported Outcome Measurement Information System

Abstract: Background: The time frame in which patients can expect functional improvement after open reduction internal fixation (ORIF) of pilon fractures is unclear. The purpose of this study was to determine the trajectory and rate at which patients’ physical function improves up to 2 years postinjury. Methods: The patients studied sustained a unilateral, isolated pilon fractures (AO/OTA 43B/C) and followed at a level 1 trauma center over a 5-year period (2015-2020). Patient-Reported Outcomes Measurement Information Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although clinically relevant differences in the postinjury functional score between patients with and without infection were detected at the 6-month time point, the longitudinal time course remains unclear. Prior research has demonstrated a functional recovery plateau occurring anywhere from 6 months to 5 years after the original injury, and so it should be assumed that patients in this cohort are continuing to improve beyond 6 months 44-47 . Second, it was possible that, over a longer time course, patients who develop an infection catch up, particularly because many patients remain under active treatment near to or during this 6-month time point.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinically relevant differences in the postinjury functional score between patients with and without infection were detected at the 6-month time point, the longitudinal time course remains unclear. Prior research has demonstrated a functional recovery plateau occurring anywhere from 6 months to 5 years after the original injury, and so it should be assumed that patients in this cohort are continuing to improve beyond 6 months 44-47 . Second, it was possible that, over a longer time course, patients who develop an infection catch up, particularly because many patients remain under active treatment near to or during this 6-month time point.…”
Section: Discussionmentioning
confidence: 99%